Experimental investigation of miniaturised rapid kit for antibody detection - Ponnalagu Arasappan Ravi. (2008)
Clinical laboratories use enzyme immunoassays for detecting antibodies, antigens, hormones and metabolites. They require sophisticated, expensive instruments and highly skilled manpower. Detection of antibody by enzyme linked immunosorbent assay tests is considerably delayed by the specimens being batched up by the laboratories and the time taken to transport specimens to the laboratories and getting back the results. Batching up of specimens for these tests is a common in centralised laboratories to reduce costs on reagents and manpower. A rapid single test diagnostic kit similar to blood glucose meters operated by semi skilled personnel have a definite place in rapid results, point of care testing and reducing healthcare costs. This project aims to design and fabricate a rapid single test miniaturised semi automated enzyme linked immunosorbent assay microfluidic chip to detect IgG and IgM antibodies to mumps virus. The chip was designed to perform the same steps as conventional enzyme linked immunosorbent assay in a microfluidic environment. The chip was fabricated in polystyrene by hot pressing with a glass die fabricated by photolithography. A polycarbonate sheet was used to cover the polystyrene chip to create the microfluidic channels. Inactivated mumps virus antigen was coated on the polystyrene chip by gentle heat fixing. Probe type spectrophotometer was used to measure the absorbance at 450 nm. The absorbance readings obtained from the micro fluidic chip correlated well with the results from a parallel run conventional enzyme linked immunosorbent assay system. A single test disposable microfluidic chip that can perform enzyme linked immunosorbent assay is a viable alternative to centralised testing.